Предмет: Алгебра,
автор: kovshirin2001
(x-5)(x+8)-(x+4)(x-1)=-36 Решите срочно Я не пойму как
Ответы
Автор ответа:
0
(x-5)(x+8)-(x+4)(x-1)=-36
х^2+8х-5х-40-(х^2-х+4х-4)=-36
х^2+8х-5х-40-х^2+х-4х+4=-36
Дальше х^2 и - х^2 сокращаются
8х-5х-40+х-4х+4=-36
3х-40+(-3х)+4=-36
3х и -3х тоже сокращаются
-40+4=-36
-36=-36
х=1
(Проверка:(1-5)(1+8)-(1+4)(1-1)
-4×9-(5×0)=-36)
Ответ:х=1.
Похожие вопросы
Предмет: Математика,
автор: zaitseva89eee
Предмет: Математика,
автор: nastya32835
Предмет: Математика,
автор: anastasiatetuhina260
Предмет: Информатика,
автор: iborzova
Предмет: Химия,
автор: lerabogdanova2